Anaerobic co-digestion of pig manure, organic fraction of municipal solid waste, fruit residues of drinks industry and cocoa residues (2023)
In Colombia, large amounts of residual biomass are generated from different productive sectors that are susceptible to be valorized in the shape of biogas, through anaerobic digestion and co-digestion processes. The present article tries the evaluation of the potential to value in the shape of biogas, four residues that are produced in the country: pig manure, cocoa industry residues, residues of the industry of bottled fruit drinks and organic fraction of municipal solid waste. In an initial stage, a non-agitated test was performed to measure the methane production potential of individual residues (anaerobic digestion) and different mixtures of three residues (anaerobic co-digestion), where the carbon nitrogen ratio (C/N) and the number of grams of volatile solids (gSv) were varied. The evaluated mixtures were constituted with two C/N levels, taking as values 25 and 35. Also, three levels of gSv were considered in the mixtures: 0.5, 1 and 2. The mixtures that obtained better results in the non-agitated tests were then evaluated in agitated experimentation to observe how this variable affects the production of biogas. Mixtures with 0.5 gSv and C/N equal to 35 were found to have the greatest potential for methanization in non-agitated tests. Agitated tests were performed with mixtures of pig manure and fruit residues. For the third component, municipal solid wastes and cocoa industry residues were used. In all the agitated tests, the potential of biogas production was higher than in the non-agitated test. Copyright © 2018, AIDIC Servizi S.r.l.